Study of penetration mechanism of labrasol on rabbit cornea by Ussing chamber, RT-PCR assay, Western blot and immunohistochemistry - Pan Guo; Nan Li; Lili Fan; Jun Lu; Boying Liu; Bing Zhang; Yumei Wu; Zhidong Liu; Jiawei Li; Jiaxin Pi; Dongli Qi (Elsevier, 2019)
Labrasol, as a non-ionic surfactant, can enhance the permeation and absorption of drugs, and is extensively used in topical, transdermal, and oral pharmaceutical preparations as an emulsifier and absorption enhancer. Recent studies in our laboratory have indicated that labrasol has a strong absorption enhancing effect on different types of drugs in vitro and in vivo. This study was performed to further elucidate the action mechanism of labrasol on the corneal penetration. In this research, the fluorescein sodium, a marker of passive paracellular transport of tight junction, was selected as the model drug to assess the effect of labrasol on in vitro corneal permeability. To investigate the continuous and real-time influence of labrasol on the membrane permeability and integrity, the Ussing chamber system was applied to monitor the electrophysiological parameters. And, furthermore, we elucidated the effect of labrasol on excised cornea at the molecular level by application of RT-PCR, Western blot, and immunohistochemical staining. The results indicated that labrasol obviously enhance the transcorneal permeability of fluorescein sodium, and the enhancement was realized by interacting with and down-regulating the associated proteins, such as F-actin, claudin-1 and β-catenin, which were contributed to cell-cell connections, respectively. Keywords: Enhanced corneal permeation, Tight junctions associated proteins, Labrasol, Ussing chamber, Western blot, Immunohistochemistry